Análise longitudinal de processos de resiliência em jovens expostos a fatores de risco na infância e adolescência - Souza, Neli de Faria Henriques Cacozza de (Universidade Federal de São Carlos, 2024)
The knowledge on resilience processes with children, adolescents, and young people in situations of social vulnerability has grown considerably around the world. However, the investigations focus, mostly, on correlational studies based on a cross-sectional design. Longitudinal research is scarce, which means that understanding the resilience processes that manifest in the transition between developmental cycles is still underexploited. The aim of this Dissertation was to analyze, through longitudinal research, the processes of resilience in young adults who were exposed to meaningful risk and vulnerability situations during childhood and adolescence. To this end, systematic literature review studies were carried out, as well as an empirical investigation. Summary, narrative reviews of the literature pointed to an increase in publication from 2015, although these papers were predominantly conducted in the United States and European countries. Data collection period varied considerably, which is associated with conceptual inaccuracies in what can be considered a longitudinal study. Furthermore, the use of questionnaires is most common in this type of research, followed by interviews and scales. In addition, another review study revealed that interpersonal relationships, engagement in formal education, subjective aspects associated with resilience, life projects and turning points are the variables most investigated and identified as promoting resilience in adolescents and young people in vulnerable situations. The empirical investigation that is part of this Dissertation refers to a qualitative study, with a longitudinal-retrospective design and conducted from a Multiple Case Study. Four young people participated in the fieldwork, aged between 25-29 years old (M = 26.75), being three women and one man. These participants were initially recruited in 2010, when they were adolescents. Inclusion criteria were: (i) being exposed to significant adversity; (ii) demonstrate resilience processes based on the evaluation of professionals who served them. Both in adolescence and adulthood, participants were involved in several stages of data collection, which culminated in an extensive qualitative database, subsequently analyzed through Thematic Analysis technique. The findings of the empirical study showed that participants were exposed to several risk factors that lasted longitudinally, from childhood to adulthood, although there were some changes in these variables. On the other hand, the participants' resilience processes were associated with the resolution of Tensions, defined as social problems that, when faced, may foster resilience processes. Some Tensions seem to have been faced since adolescence, while others were only resolved when the participants were adults. Furthermore, a new Tension was identified in this Dissertation - Ability to nurture life projects - which requires additional investigations in the future to be confirmed, refuted, or reformulated it. It is expected that this research report may contribute to the advancement of the debate on longitudinal research on resilience processes, as well as contribute to understanding the needs of adolescents and young people who experience chronic social adversities.
Longitudinal analysis of resilience processes in young people exposed to risk factors in childhood and adolescence
Keywords: Resiliência; Adolescentes; Jovens; Pesquisa longitudinal; Resilience; Adolescents; Young people; Longitudinal research; CIENCIAS HUMANAS::PSICOLOGIA